2010
DOI: 10.1007/s10661-010-1786-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selected heavy metals on the histopathology of different tissues of earthworm Eudrillus eugeniae

Abstract: Laboratory-scale experiments were conducted to determine the effect of heavy metals viz. copper (Cu), cadmium (Cd), chromium (Cr), lead (Pb), and zinc (Zn) on the different vital tissues of earthworm Eudrillus eugeniae such as head, gizzard, clitellum, and intestine after the worms were placed in municipal solid waste (MSW) substrate spiked with heavy metals in the concentration range of 0.05 g/kg to 1.0 g/kg of the waste for Cu, Cr, PB, and Zn and 0.05 g/kg for Cd. The experiments were conducted for 100 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…5 ) also exhibited interesting outcome. It was reported previously that the exposure to Cd should have caused significant damage to the intestinal wall of Eudrillus euginae 30 . Contrary to such finding, we were unable to find such abnormality in Eisenia fetida .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…5 ) also exhibited interesting outcome. It was reported previously that the exposure to Cd should have caused significant damage to the intestinal wall of Eudrillus euginae 30 . Contrary to such finding, we were unable to find such abnormality in Eisenia fetida .…”
Section: Discussionmentioning
confidence: 93%
“…Simultaneously, another set of gut cleaned earthworms were collected after 60 days and killed by freezing, washed with de-ionized water, and used for histological analysis by adopting the procedure of Sharma and Satyanarayan 30 . Briefly, the earthworm tissues were fixed in Bouin’s fluid for 24 hrs and dehydrated in graded alcohol from 30% to 100% followed by xylene for 10 minutes and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…for E. albidus the LC 50 (21 days, survival) and EC 50 (42 days, reproduction) for Cr(NO 3 ) 3 ⋅9H 2 O were 1620 and 637 mg Cr/kg, respectively (Lock and Janssen, 2002), and for Eisenia fetida the LC 50 (14 days) for CrCl 3 ⋅6H 2 O ranged between 1656 and 1902 mg Cr/kg in 10 different soils (Sivakumar and Subbhuraam, 2005). On the other hand, for Eudrillus eugeniae, not a standard species/test, a longer exposure duration of 100 days-1000 mg Cr/kg showed severe destruction of tissues of the exposed organisms in municipal solid wastes (Sharma and Satyanarayan, 2011). Also a study exposing Eisenia andrei to chromium nitrate showed significant effects on reproduction at concentrations of 100 mg Cr/kg and higher (van Gestel et al, 1993), indicating higher toxicity of Cr to this species.…”
Section: Discussionmentioning
confidence: 98%
“…After the uptake phase (14 days in the spiked soil), surviving animals were transferred to clean soil to evaluate the elimination phase (14 days in clean soil). Sampling of 5 replicates was done at 7 time points for the uptake phase (days 0, 1, 2, 4, 7, 10, 14) and 6 time points for the elimination phase (days 15,16,18,21,24,28) to analyze internal Cr concentration. At days 0, 14, and 28, controls with non-spiked soil were also sampled.…”
Section: Methodsmentioning
confidence: 99%
“…Survival and reproduction are the most studied endpoints when assessing the effects of Cr on soil organisms such as enchytraeids, earthworms, and springtails [8,[15][16][17][18][19][20][21]. Enchytraeids present a ubiquitous distribution and large abundance in most soils and different ecosystems, being one of the most relevant soil organisms [22].…”
Section: Introductionmentioning
confidence: 99%